The IL-33/ST2 pathway contributes to intestinal tumorigenesis in humans and mice - Mertz, Kirsten D. (Oncoimmunology, 2015)
Colorectal cancer (CRC) develops through a multistep process and is modulated by inflammation. However, the inflammatory pathways that support intestinal tumors at different stages remain incompletely understood. Interleukin (IL)-33 signaling plays a role in intestinal inflammation, yet its contribution to the pathogenesis of CRC is unknown. Using immunohistochemistry on 713 resected human CRC specimens, we show here that IL-33 and its receptor ST2 are expressed in low-grade and early-stage human CRCs, and to a lesser extent in higher-grade and more advanced-stage tumors. In a mouse model of CRC, ST2-deficiency protects from tumor development. Moreover, bone marrow (BM) chimera studies indicate that engagement of the IL-33/ST2 pathway on both the radio-resistant and radio-sensitive compartment is essential for CRC development. Mechanistically, activation of IL-33/ST2 signaling compromises the integrity of the intestinal barrier and triggers the production of pro-tumorigenic IL-6 by immune cells. Together, this data reveals a tumor-promoting role of IL-33/ST2 signaling in CRC.